Western society and the Church in the Middle Ages - Southern, R. W. (Richard William) (England Penguin Books, 1970)
St. Anselm - Astrology - St. Augustine - St. Thomas A'Becket - St. Benedict - Byzantine Empire - Crusades - Dominicans (origin of) ; St. Francis - Heresy - Thomas Aquinas - Women in Religion - Women and the church__
Keywords: Church history -- Middle Ages, 600-1500. Civilization, Medieval. Christianity -- History -- Middle Ages, 600-1500.